Penerapan Flipped Classroom Berbasis Teknologi Informasi pada Mata Pelajaran Fiqih di MTs Al-Chusnaniyah Surabaya - Ubaidillah, Muhammad (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2019)
E-Learning is one of the breakthroughs in education that requires information technology. Various online learning models began to be developed. For example blended learning, distance learning (distance learning) and flipped learning. Online learning is basically trying to innovate and change the paradigm in learning. One model of online learning that is currently quite a lot of learning in educational research is reverse learning. Reverse classes are learning held in class with online learning. In turning the lassroom things that are usually done in the classroom such as explaining the material, giving assignments, exercises and homework are transferred to online learning. This research was conducted with development research design. This study aims to study the differences in student learning outcomes through pretest and posttest in students and student learning outcomes also aims to determine the level of student self-confidence. The application of Information Technology-Based Flipped Classroom learning model to classroom learning outcomes and the increase in self-confidence of class VIII students in Fiqh Subjects in MTs Al-Chusnaniyah Surabaya is relatively effective.